Analysis of the Results of Physical Training for Elementary School Students at the 50th Elementary School in Quwa County, Fargo. - N.Mamadjanov; M.Bakirova (Genius Journals, 2023)
The 50th elementary school in Quwa County reported on the results of pedagogical and scientific research using special mathematical and statistical methods
Keywords: Physical training; level of physical training; sports tests; mokisimon running